Preliminary Testing of a Color-based Test Kit Detector for Bioplastics - Farrah, Wong; Noor Fazilah, Rahmansyah; Sariah, Abang; Chung, Seng Kheau; Aroland, Kiring; Jamal, Ahmad Dargham; Rosalam, Sarbatly (Springer, Singapore, 2024)
Plastic was invented in 1907 by Leo Baekeland who is a Belgian-American Chemist. Since then, his creation has paved the way for the future of polymers. Nowadays, plastics come in different types with multitude of uses ranging from household storage purpose to medical packaging means. However, it also has a negative impact on humanity as well, particularly on the environment and bioplastics is noticeably would be the way forward to achieve a sustainable environment. Bioplastics is synthesized from biomass or other natural material as the new alternative to plastic as it degrades much faster. Eventually, a bioplastic testing kit will be necessary, especially in the market where the use of plastic will be regulated. A prototype test kit based on Arduino and a color sensor was developed to distinguish different plastic types based on their distinct color reactions to specific chemical reagents. The fundamental question was how to create a feasible way to distinguish between cellulose-based, starch-based, biodegradable, and conventional plastics and deal with the accompanying challenges. The reagents applied to the samples included iodine, iodine-CaCl2, and Schultze reagents. Notably, the cellulose-based and starch-based straw samples exhibited a dark purple color change with iodine and dark blue with iodine-CaCl2 and Schultze reagent. In contrast, starch-based singlet bags exhibited brown transforming into purple with iodine and Schultze reagents. Besides, biodegradable, and conventional plastics displayed no color changes with any reagents. The test kit has shown a promising way to assist consumers to make a more informed decision through a simple test.